Viability of ESports Service Provider in the Local Market in the Second District of Albay: Opportunity of Investment - Magcalen, Willard Nathan (JPAIR Multidisciplinary Research, 2023)
Online gaming is now a spectator sport, thanks to ESports. The experience is similar to watching a professional athletic event, but viewers see video gamers compete against one another instead of a physical contest. This qualitative research determined ESport’s viability status in the 2nd District of Albay. It sought to determine the status of the business requirements needed to establish an ESports business along with Network Infrastructure, Legal requirements, and Stability of power. It also evaluates the viability of ESports in the local market regarding technical and economic requirements. It focuses on the challenges of the Department of Information and Communication Technology (DICT) in providing opportunities for investment in e-services. Lastly, this research proposed a business process mapping model canvas that potential investors can adopt. The study revealed limited information regarding the stability of power in the context of ESports. No specific information was provided regarding how power stability is ensured or what measures are taken to ensure uninterrupted power supply during ESports tournaments. Likewise, power outages and fluctuations can cause disruptions and affect the gameplay, leading to frustration for players and viewers. Regularly maintaining electrical equipment and wiring is also necessary to prevent power outages and hazards. Technically ESports is viable, despite challenges that may be encountered, and does create a business model canvas.